2006
DOI: 10.1111/j.1934-6093.2006.tb00285.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Control of Flexible Joint Robots

Abstract: The robotics literature of the last two decades contains many important advances in the control of flexible joint robots. This is a survey of these advances and an assessment for future developments, concentrated mostly on the control issues of flexible joint robots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(77 citation statements)
references
References 150 publications
0
67
0
1
Order By: Relevance
“…Several control strategies [13][14][15] have been proposed for the control of manipulators with joint flexibility based on reduced-order system models derived in separate time-scales using singular perturbation techniques. However, the problems associated with parameter variations have not been addressed in these works.…”
Section: Introductionmentioning
confidence: 99%
“…Several control strategies [13][14][15] have been proposed for the control of manipulators with joint flexibility based on reduced-order system models derived in separate time-scales using singular perturbation techniques. However, the problems associated with parameter variations have not been addressed in these works.…”
Section: Introductionmentioning
confidence: 99%
“…The control of robot faces significant difficulties, with regard to such a complicated system, various controllers have been developed [1], such as adaptive controllers [2][3][4], robust controllers [5][6][7] and controllers based on the theory of variable structure [8][9][10][11]. However, the applicability of these controllers to practical robot is limited because the assumption of perfect rigidity is never satisfied exactly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, frequency analysis of the data using FFT better reveals the dominant frequency of the system in the course of motion. As shown in Figure 4, when EA is multiplied by 10, with a good approximate, the most dominant or the lowest natural frequency is multiplied by p 10. In addition, an increase in the location of the lowest natural frequency decreases the amplitude vibration.…”
Section: Dynamic Response Of the Exible Robotmentioning
confidence: 99%
“…They showed that asymptotic stability of the closed loop system can be guaranteed using a composite control comprising a rigid model based controller and a PD term, proportional to the time derivative of the tension [9]. A survey of the control of exible joint robots is provided in [10], where di erent approaches such as composite control and the concept of integral manifold are compared.…”
Section: Introductionmentioning
confidence: 99%